(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Any discrimination or exclusion based on sexual orientation for the purpose of reducing equality before the law, as well as providing preferential treatment on these grounds, constitutes sexual orientation discrimination . This paper will, inter alia, address the rights of same-sex partners vis-a-vis the rights of heterosexual partners, with the aim of analyzing the current stage of the European perspective in the area where the legal arrangements of certain EU Member States (hereinafter: MS) will be presented by a comparative method. It is precisely these issues that have been decided by the Court of Justice of the European Union (hereinafter: CJEU), from which the major problems in the area of sexual orientation discrimination are identified. In the view of the CJEU, in order for a treatment to be characterized as discrimination on the basis of sexual orientation, a community of same-sex partners must be legalized in a MS. Only when such a legal framework exists can the CJEU decide whether there is a basis for discrimination. Such an interpretation begs the question, what about states that do not have any legal framework that recognizes the same-sex life community? The first part of the paper will analyze international and European standards of protection against sexual orientation discrimination, and after that, the current level of same-sex rights in the EU will be briefly presented. The second part of the paper will be based on analysis of the impact of CJEU decisions on changes in Romanian legislation in the field of recognizing the effect of same-sex marriage, concluded in another MS, as well as an analysis of the process of recognizing the effect of same-sex marriage in the Republic of Croatia (hereinafter: Croatia) In addition, the paper will also analyze the judgment of the Constitutional Court of the Republic of Croatia (hereinafter: CCRC) regarding discrimination on the grounds of sexual orientation observed in the positive regulation governing the issue of foster care. Based on these analyzes, de lege ferenda guidelines will be given at the end of the paper in order to reduce the possibility of sexual orientation discrimination.